Identifikasi Potensi Kunjungan Wisatawan Mancanegara pada Pos Lintas Batas Builalo di Provinsi Nusa Tenggara Timur - Maulana, Addin (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2019)
Cross-border posts have a big role in contributing foreign tourists to Indonesia, but until now the records carried out are still less optimal. This study aims to identify the potential for tourist visits through the Builalo’s Cross-border Post, so that the development of tourism that depends on this post can be further optimized. By using descriptive methods where data is collected through documentation studies, field observations, and interviews. This research has successfully identified that the Builalo Cross-border Post located in East Nusa Tenggara Province has the potential for foreign tourists to visit an average of 5.55 per day or 2,026 foreign tourists per year. Foreign tourist visits through this gate are strongly influenced by the Market Day which is held every Thursday, where that day always has the highest peak visit in 1 week, and it is estimated that the average visit on that day is 23.7. foreign tourist visits. Inadequate facilities and infrastructure are the most serious challenges in the development of Tourism in the area adjacent to this gate. Because visiting friends or relatives is another main goal besides visiting market days, it creates more economic activity (trade, festivals, etc.) and an increase in supporting facilities is felt very necessary. Key words: Cross-border Post, Tourism, International Tourist Arrivals.